Parenting Education in Islamic Families within the Framework of Family Resilience in Aceh, Indonesia - Abubakar, Bahrun; Sanusi, Sanusi; Razali, Razali; Yeniningsih, Taat Kurnita; Mujiburrahman, Mujiburrahman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Parenting education plays an important role in fostering healthy family character, supporting child development, and ensuring family resilience. This research aims to apply Islamic values in parenting practices, examine the role of culture and community support, understand challenges and parenting strategies, analyze gender roles, and assess the effectiveness of parenting education programs in Aceh. The study uses qualitative methods, and analysis using parenting theory. Semi-structured interviews and literature studies were used to collect data. The analysis includes coding of qualitative data, classification, and interpretation. Ethical considerations are enforced throughout the research process, to ensure respondent consent, privacy, and confidentiality and address potential researcher bias. The results of the study concluded that parenting education requires support from Islamic values, culture, community encouragement, fair and good parenting, gender roles, and parenting education programs. Parenting education for Islamic families in Aceh based on religious values (such as monotheism and piety) and Islamic culture has been proven to create family resilience. The tsunami incident is clear evidence of the resilience of the Acehnese family based on Islamic values and religious culture. On the other hand, religious leaders and educators can encourage and enhance this parenting education model in society. The findings of this study have practical implications for developing parenting education programs and interventions that are sensitive to values and culture in promoting well-being, the Islamic family model and family resilience in Aceh, Indonesia.